The Effect Of Using Audio Lingual Method In The Listening Comprehension Of Grade Ten Students Of SMA Swasta Kampus Nommensen Pematang Siantar - Andrian Petrus Sirait; David Berthony Manalu; Basar Lolo Siahaan (Jurnal Ilmu Pendidikan dan Sosial, 2024)
The aim of this research is to find out whether there is a significant effect of using the audio-lingual method on the listening comprehension of tenth grade students at Nommensen Private High School, Pematang Siantar Campus. In addition, the aim of this research is to make teachers consider appropriate methods that they can implement in the classroom to teach students about listening comprehension. Therefore, teachers must pay attention to the appropriate methods that can be used to achieve maximum listening comprehension indicators. Another aim of this research is to help students understand listening comprehension material using the Audio Lingual Method and to entertain them with various ways of teaching in the learning process by providing them with music or other educational entertainment to increase their motivation in learning and creating. they are interested in listening to the material to achieve good habits from the learning process in the classroom which is the main goal of the Audio-Lingual Method. This research is quantitative research with the form of an experimental design. This research involves two variables; there is an independent variable, namely the Audio Lingual Method (X) and a dependent variable, namely students' listening comprehension (Y). In this research, the researcher used a purposive sampling technique to select the sample, and decided class X-3 as the Experiment Class and X2 as the Control Class to be the sample for this research where the number of students in the class was 30 students. Researchers also use research instruments which are divided into two instruments, namely instrument blueprints and instrument calibration. Researchers use tests, observation, and documentation as data collection methods. After calculating the average and standard deviation of the two classes, the researcher uses the t-test formula, the results of the t-test must be higher than the t-table with a significance level of 5% (2.265 > 1.680). Based on the research findings, the researcher concluded that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. So, it can be concluded that the use of the audio lingual method influences the listening comprehension of tenth grade students.